Ethnic identity of children in ethnic-mixed families: thematic analysis - Yem, N.B.; Tsoy, L.G. (Journal of Oriental Studies, 2021)
The ethnic identity of children in ethnically mixed families is of considerable academic interest. In order to determine the main thematic problems in this work, the author conducts a historiographic study of the degree of study of the ethnic identity of children in ethnically mixed families. On the basis of these historiographic sources, special studies of the problem under study were systematized by the method of problem-chronological and comparative analysis. In particular, they analyzed research in the Google Scholar search engine related to the issues of children in ethnically mixed marriages in an English-language search. The article systematized problem blocks: theories of ethnic and racial categories in identification, the influence of the place and stages of socialization on ethnic identity, the role of social practice in the formation of ethnic identity. Thus, the author has identified three areas of special research into the problem of ethnic identity of children with dual ethnicity as a result of interethnic marriage. Thematic analysis of the texts revealed insufficient knowledge of ethnic identity in ethnically mixed families, in particular Koreans abroad. This analysis has a number of limitations, which set the task for further consideration in the context of studying the peculiarities of the ethnic identity of foreign Koreans, taking into account the specifics of the history and culture of the host country. Key words: ethnic identity, interethnic families, historiography, special studies, dual ethnicity.